Distributed . NET with Microsoft Orleans : Build Robust and Highly Scalable Distributed Applications Without Worrying about Complex Programming Patterns - Muthiyalu, Bhupesh Guptha (Packt Publishing, Limited, 2022)
Adopt an effortless approach to avoid the hassles of complex concurrency and scaling patterns when building distributed applications in .NET Key Features Explore the Orleans cross-platform framework for building robust, scalable, and distributed applications Handle concurrency, fault tolerance, and resource management without complex programming patterns Work with essential components such as grains and silos to write scalable programs with ease Book Description Building distributed applications in this modern era can be a tedious task as customers expect high availability, high performance, and improved resilience. With the help of this book, you'll discover how you can harness the power of Microsoft Orleans to build impressive distributed applications. Distributed .NET with Microsoft Orleans will demonstrate how to leverage Orleans to build highly scalable distributed applications step by step in the least possible time and with minimum effort. You'll explore some of the key concepts of Microsoft Orleans, including the Orleans programming model, runtime, virtual actors, hosting, and deployment. As you advance, you'll become well-versed with important Orleans assets such as grains, silos, timers, and persistence. Throughout the book, you'll create a distributed application by adding key components to the application as you progress through each chapter and explore them in detail. By the end of this book, you'll have developed the confidence and skills required to build distributed applications using Microsoft Orleans and deploy them in Microsoft Azure. What you will learn Get to grips with the different cloud architecture patterns that can be leveraged for building distributed applications Manage state and build a custom storage provider Explore Orleans key design patterns and understand when to reuse them Work with different classes that are created by code generators in the Orleans framework Write unit tests for Orleans grains and silos and create mocks for different parts of the system Overcome traditional challenges of latency and scalability while building distributed applications Who this book is for This book is for .NET developers and software architects looking for a simplified guide for creating distributed applications, without worrying about complex programming patterns. Intermediate web developers who want to build highly scalable distributed applications will also find this book useful. A basic understanding of .NET Classic or .NET Core with C# and Azure will be helpful.